2015
DOI: 10.1016/j.ejso.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conversion gastrectomy following docetaxel, cisplatin, and S-1 therapy in potentially resectable stage IV gastric cancer

Abstract: Patients with potentially resectable disease had a remarkably good prognosis among stage IV gastric cancer patients, and might be ideal candidates for conversion gastrectomy following DCS therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 23 publications
2
61
1
1
Order By: Relevance
“…Some of previous studies suggested that SRCC is less chemo‐sensitive than non‐SRCC cancers, so the value of palliative gastrectomy plus chemotherapy may be even higher in stage IV gastric SRCC than NOS. In addition, several recently published studies proved that improved long‐term survival was observed among stage IV GC patients who underwent conversion surgery (primary tumor resection performed in initially unresectable metastatic cancer after responding to chemotherapy) . This also cast light on the therapeutic role of palliative surgery strategies in stage IV gastric SRCC patients.…”
Section: Discussionmentioning
confidence: 94%
“…Some of previous studies suggested that SRCC is less chemo‐sensitive than non‐SRCC cancers, so the value of palliative gastrectomy plus chemotherapy may be even higher in stage IV gastric SRCC than NOS. In addition, several recently published studies proved that improved long‐term survival was observed among stage IV GC patients who underwent conversion surgery (primary tumor resection performed in initially unresectable metastatic cancer after responding to chemotherapy) . This also cast light on the therapeutic role of palliative surgery strategies in stage IV gastric SRCC patients.…”
Section: Discussionmentioning
confidence: 94%
“…However, data from the eastern experience and the possibility of more extensive surgeries with low morbidity have led the physicians to be more aggressive in the treatment of metastatic disease. Curative outcomes have been reported with an R0 resection in potentially/marginally resectable cases, although they are initially metastatic diseases, referred to as conversion treatment (30)(31)(32). Although potentially resectable cases, such as single liver metastasis or 16a2-b1 paraaortic lymph node metastasis are technically suitable for surgical resection, we prefer preoperative chemotherapy followed by surgical resection.…”
Section: Management Of Metastatic Diseasementioning
confidence: 99%
“…However, several novel combined chemotherapy regimens occasionally allow conversion of initially unresectable gastric cancer to resectable cancer. Additional (conversion) surgery after response to chemotherapy results in long-term survival in selected patients (2)(3)(4)(5)(6)(7). We have previously reported that patients with unresectable gastric cancer obtained survival benefit from S-1-based chemotherapy, and subsequent conversion surgery (8).…”
mentioning
confidence: 99%